2001
DOI: 10.1159/000051081
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cells Influence Monocyte Response to LDL as well as Their Adhesion and Transmigration in a Coculture Model of the Arterial Wall

Abstract: We investigated the possible interference of smooth muscle cells with monocyte response to LDL as well as with their adhesion and transmigration in a coculture of porcine endothelial and smooth muscle cells. Lysophosphatidylcholine (LPC), a component of oxidized LDL (oxLDL), stimulated the adhesion of THP-1 cells to endothelial cells both in mono- and in coculture with smooth muscle cells. When THP-1 cells were incubated with endothelial cells in the presence of copper oxLDL, their adhesion was increased, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
2
13
2
Order By: Relevance
“…Since GRO-a and MCP-1 have been shown to be leukocyte adhesion factors on ECs (Weber et al, 1999), our results on GRO-a and MCP-1 gene induction in ECs cocultured with SMCs under static condition may explain the findings of and Kinard et al (2001) that leukocyte adhesion greatly increased in such cocultures. Though the mechanisms by which SMCs in coculture augment the GRO-a and MCP-1 gene expressions in ECs under static condition remain unclear, the importance of specific interaction between the cocultured ECs and SMCs in regulating EC gene expression was indicated by the lack of induction of these genes in ECs when ECs were cocultured with fibroblasts instead of SMCs.…”
Section: Discussionsupporting
confidence: 64%
“…Since GRO-a and MCP-1 have been shown to be leukocyte adhesion factors on ECs (Weber et al, 1999), our results on GRO-a and MCP-1 gene induction in ECs cocultured with SMCs under static condition may explain the findings of and Kinard et al (2001) that leukocyte adhesion greatly increased in such cocultures. Though the mechanisms by which SMCs in coculture augment the GRO-a and MCP-1 gene expressions in ECs under static condition remain unclear, the importance of specific interaction between the cocultured ECs and SMCs in regulating EC gene expression was indicated by the lack of induction of these genes in ECs when ECs were cocultured with fibroblasts instead of SMCs.…”
Section: Discussionsupporting
confidence: 64%
“…These mediators can mutually affect functions through receptor mediation, myoendothelial bridges between ECs and SMCs, establishment of gap junctions and changes in the extracellular matrix components (1416). The EC, SMC and mononuclear cell (MC) co-culture system, established on a polyethylene microporous membrane has revealed that the direct contact between ECs and SMCs serves a key function in MC adhesion and infiltration, and also accelerates the adhesion dynamics of THP-1 cells with ECs (17). MC infiltration, foam cell formation, the expression of interleukin (IL)-8 in SMCs and collagen deposition have been observed in the EC-SMC co-culture system, using fibrin gel as the scaffold (18).…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of monocytederived macrophages under endothelium hyperplasia and the migration of arterial SMC contribute to inflammation and the development of intimal hyperplasia during atherosclerosis. In addition to endothelial cells, vascular SMC also play an important role in the development and progress of atherosclerosis [9,19,20] . It is known that the damage of endothelium-dependent relaxation of blood vessels and the formation of the atherosclerotic plaque caused by hypercholesterolemia is related to circulating ox-LDL.…”
Section: Discussionmentioning
confidence: 99%